Radiation-responsive polymers: a novel spectral approach to investigate ultrahigh molecular weight polyethylene modifications using Grunwald-Letnikov and Caputo fractional order derivatives - Saeed, Muhammad; Muddassar, M.; Sajjad Mehmood, M.; Siddiqui, N. (Revista Mexicana de Física, 2025)
The impact of gamma radiation on Ultrahigh Molecular Weight Polyethylene (UHMWPE) using fractional differential transformations of FTIR spectra has been probed during the current study. The gamma irradiated samples of UHMWPE for doses of 0, 25, and 50 kGy have been tested with FTIR spectroscopy, and subsequent to testing each spectrum has been analyzed with fraction order differentiation ranging from 0.5 to 1. The exhibited significant shifts in absorbance due to radiation-induced physical and chemical changes, including C=C unsaturation, C=O carbonyl absorption, and variations in CH2 bending and stretching frequencies are clearly evident even at the lowest order of applied transformation. The weak bands in spectral regions 800 − 1100 cm−1 because of gamma radiation caused peak splitting in the 800 − 1100 cm−1 region, attributed to the conversion of vinyl groups into vinylidene and trans-vinylene groups, have also been observed at all orders of applied transformations. It is, therefore, fractional differential transformations thus proved to be a potential methodology for in depth spectra analysis of radiation responsive polymers like UHMWPE with a minimal information loss during the transformation. This is also confirmed by sensitivity and specificity analysis that demonstrated that lower-order transformations are effective for accurate spectral characterization.